INVESTIGATIONS ON SEMEN QUALITY AND FREEZABILITY OF CHOLISTANI BREEDING BULLS - A PRELIMINARY STUDY FROM CHOLISTAN DESERT OF PAKISTAN - U. Farooq; A. Ijaz; N. Ahmad; H. Rehman; H. Zaneb (Journal of Animal and Plant Sciences, 2013)
The present study was designed to generate a preliminary data regarding the semen quality and freezability of Cholistani breeding bulls (n = 06) maintained at the Semen Production Unit, Karaniwala, Punjab, Pakistan. Semen fromexperimental bulls was collected weekly from October to December, 2011, using homosexual mount, with an artificial vagina. A total of 132 ejaculates, with 22 ejaculates per bull, were collected. The mean ejaculatory volume (ml), mass activity (Scale 0-5), individual sperm motility (%) and sperm concentration (million/ml) were 4.45 ± 0.76, 1.94 ± 0.14, 64.38 ± 2.64 and 918.05 ± 65.79, respectively. The fresh semen attributes in terms of live and morphologically normal sperm, and those with intact acrosome (acrosome integrity) revealed mean values of 84.60 ± 1.27, 83.97 ± 0.61 and 83.85 ± 0.54%, respectively. Semen was diluted by slow and one step method in Tris egg yolk extender, filled in 0.5 ml straws, equilibrated at 4°C for 6 hrs, frozen and stored in liquid nitrogen for 24 hrs. Post thaw assessment in terms of sperm motility, live and morphologically normal sperm and acrosome integrity revealed quite encouraging results. This preliminary data envisages for further studies with a larger sample size expanded over all seasons and in correlation to age and testicular biometry in order to establish seasonality of reproduction (if any) in the Cholistani breed of cattle.
Keywords: Semen quality; freezability; breeding bulls; Cholistani